2013
DOI: 10.1088/0004-637x/773/2/147
|View full text |Cite
|
Sign up to set email alerts
|

A Tight Connection Between Gamma-Ray Outbursts and Parsec-Scale Jet Activity in the Quasar 3c 454.3

Abstract: We analyze the multi-frequency behavior of the quasar 3C 454.3 during three prominent γ -ray outbursts: 2009 Autumn, 2010 Spring, and 2010 Autumn. The data reveal a repeating pattern, including a triple flare structure, in the properties of each γ -ray outburst, which implies similar mechanism(s) and location for all three events. The multi-frequency behavior indicates that the lower frequency events are co-spatial with the γ -ray outbursts, although the γ -ray emission varies on the shortest timescales. We de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
113
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(134 citation statements)
references
References 85 publications
19
113
0
Order By: Relevance
“…If the shock/ disturbance is slightly faster, then it is plausible to build up the toroidal component and lead to significant polarization variations such as the PA rotations; but in both cases, the flux will not increase sufficiently to produce a flare. Such polarization variations with no obvious flares are consistent with some observations (e.g., Itoh et al 2013;Jorstad et al 2013). However, Kirk et al (2000) and Achterberg et al (2001) have shown that for relativistic shocks, the hardest obtainable particle power-law index is approximately…”
Section: Discussion and Summarysupporting
confidence: 92%
“…If the shock/ disturbance is slightly faster, then it is plausible to build up the toroidal component and lead to significant polarization variations such as the PA rotations; but in both cases, the flux will not increase sufficiently to produce a flare. Such polarization variations with no obvious flares are consistent with some observations (e.g., Itoh et al 2013;Jorstad et al 2013). However, Kirk et al (2000) and Achterberg et al (2001) have shown that for relativistic shocks, the hardest obtainable particle power-law index is approximately…”
Section: Discussion and Summarysupporting
confidence: 92%
“…The highest levels of the emission Mg II line flux and γ-ray outburst happens when a jet component passes through (or ejected from) the radio core of 3C 454.3. This remarkable event was also confirmed in consequent studies (Isler et al 2013;Jorstad et al 2013).…”
Section: Location Of γ-Ray Emission In the Jetsupporting
confidence: 72%
“…In addition, when knot K11b encountered stationary knot A2, it brightened and became more highly polarized (Figure 19 The higher polarization when superluminal knots K11b and K12b reached stationary knot A2 could have been caused by an increase in the strength and order of the magnetic field from compression by a stationary shock corresponding to A2. This situation bears a striking resemblance to that in 3C 454.3 when new knot K09 encountered stationary knot C (Wehrle et al 2012b;Jorstad et al 2013). Just as in the case of 3C 454.3, the stationary knot's EVPA is always nearly aligned with the jet direction, a signature of a transversely oriented shock with magnetic field compressed along the shock front (Hughes et al 1985(Hughes et al , 1989.…”
Section: Kinematics Of the Parsec-scale Radio Jet And Relationship Tomentioning
confidence: 61%